Ethnic Identity, Self-Determination, and Human Rights: Majoritan Democracy Re-examined - Buendia, Rizal (Kasarinlan: Philippine Journal of Third World Studies; Vol 8 No 4 (1993): The NDF at 20: A Front United?, 2008)
The non-recognition of the rights of ethnic groups to self-determination under international law and by the UN stems from the apprehension of states and governments that if minority peoples hold such a right, existing states might break up trough secession, irredentism, or political independence. Undeniably, the states consider their interest far more important at the present time than any human right.